FINANCIAL PERFORMANCE, MACROECONOMIC FACTORS AND COMPANY CHARACTERISTICS IN CONSUMER GOODS COMPANY IN INDONESIA - Suseno, Mohamad Ali (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The company's performance in the consumer sector had heavily influenced by the company's external and internal conditions. This research aims to analyze the influence of macroeconomic factors and company characteristics on the company's financial performance in consumer goods sector companies. The population in this research is a consumer goods sector company listing on the Indonesia Stock Exchange. Sampling techniques using purposive sampling and data analysis methods using multiple regression analyses. The results showed that the macroeconomic factors had no significant effect on the company's performance. The company's significant characteristics are the debt level of the company. The company's debt level of leverage has a negative and significant impact on the company's performance, suggesting that the higher the company's debt will decrease the company's performance. This research has limitations on samples that are only consumer goods companies, so it can not be generalized in other business sectors.